Copper–cobalt catalysts supported on mechanically mixed HZSM-5 and γ-Al2O3 for higher alcohols synthesis via carbon monoxide hydrogenation. Issue 26 (9th May 2019) - Ge, Xuan; Sun, Hang; Dong, Kun; Tao, Yanqi; Wang, Qi; Chen, Yazhong; Zhang, Genlei; Cui, Peng; Wang, Ye; Zhang, Qinghong
Abstract : CuCo bimetallic catalysts over the mixed supports showed smaller average particle size, better dispersion of cobalt and copper species, and good activity for higher alcohols synthesis. Abstract : Mechanically mixed γ-Al2 O3 and HZSM-5 (Si/Al = 50) with different mass ratio were utilized as support for Cu–Co higher alcohol synthesis catalysts prepared through incipient wetness impregnation. The textural and structural properties were studied using Ar low temperature adsorption and desorption, H2 -temperature programmed reduction (H2 -TPR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM) and catalytic performance measurements. The results indicated that the mechanically mixed HZSM-5 and γ-Al2 O3 supported copper–cobalt catalysts were superior to either γ-Al2 O3 or HZSM-5 supported ones with the same metal loading. The results revealed that using HZSM-5 and γ-Al2 O3 mechanically mixed benefited the dispersion of metallic phases and stronger synergetic functions between smaller nanoparticles containing copper and/or cobalt, which is essential for HAS from CO hydrogenation. Under working conditions of P = 5.0 MPa, T = 300 °C, V (H2 ) :  V (CO) :  V (N2 ) = 4 : 2 : 1 and GHSV = 7200 mL g −1 h −1, mechanically mixed HZSM-5 and γ-Al2 O3 supported catalysts showed higher catalytic activity than those over single support. For CuCo catalysts upon support containing 50.0 wt% HZSM-5 and 50.0 wt% γ-Al2 O3, the CO conversion was 21.3% and the C2+ alcohol selectivity was 41.8%.